2022
DOI: 10.4103/ijo.ijo_2193_21
|View full text |Cite
|
Sign up to set email alerts
|

Association of dry eye disease with smoking: A systematic review and meta-analysis

Abstract: There is conflicting evidence for the association between smoking and dry eye disease (DED). We conducted a meta-analysis to determine the true relationship between smoking and DED. A systematic literature search was performed using electronic databases, including PubMed, Embase and Cochrane Library, till August 2021 to identify observational studies with data on smoking as risk factor of DED. Quality assessment of the included studies was conducted using Joanna Briggs Institute (JBI) critical appraisal checkl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
6
0
2
Order By: Relevance
“…Some of these preventive treatments were studied in a recent study to examine the application of artificial tears and contact lenses, concluding that they significantly reduced DED symptoms [ 29 ]. In concordance with our findings regarding the association between secondhand smoke and DED, a systematic review of 22 studies concluded that smoking may not be considered a risk factor for developing DED, and that there is conflicting information regarding smoking's role in DED development [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Some of these preventive treatments were studied in a recent study to examine the application of artificial tears and contact lenses, concluding that they significantly reduced DED symptoms [ 29 ]. In concordance with our findings regarding the association between secondhand smoke and DED, a systematic review of 22 studies concluded that smoking may not be considered a risk factor for developing DED, and that there is conflicting information regarding smoking's role in DED development [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to these findings, Wangkaew et al revealed no statistical difference between SSc patients and healthy subjects after adjusting for the use of xerogenic drugs and smoking, suggesting that the utilization of drugs with anticholinergic side-effects and smoking may also be associated with higher dry eye symptom scores in SSc patients. [ 20 , 21 ] Keratoconjunctivitis, skin changes of the eyelid, uveitis, episcleritis, weakening of the extraocular muscles, scleritis, glaucoma, peripheral ulcerative keratitis, enophthalmos, and cataract are some of the other clinical symptoms. One-third of SSc patients had retinal abnormalities on fundus examination, according to a cross-sectional investigation evaluating retinal involvement [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our study, we found that higher OSDI scores were reported in subjects in the medical field, teaching assistants, and non-smokers. Regarding the association between DED and smoking, Tariq et al conducted a meta-analysis, and the results indicate that smoking doesn't increase the risk for DED [ 19 ].…”
Section: Discussionmentioning
confidence: 99%